Genetically Encoded Calcium Indicators Can Impair Dendrite Growth of Cortical Neurons - Gasterstädt, Ina; Jack, Alexander; Stahlhut, Tobias; Rennau, Lisa-Marie; Gonda, Steffen; Wahle, Petra (Frontiers in Cellular Neuroscience, 2020)
A battery of genetically encoded calcium indicators (GECIs) with different binding kinetics and calcium affinities was developed over the recent years to permit long-term calcium imaging. GECIs are calcium buffers and therefore, expression of GECIs may interfere with calcium homeostasis and signaling pathways important for neuronal differentiation and survival. Our objective was to investigate if the biolistically induced expression of five commonly used GECIs at two postnatal time points (days 14 and 22–25) could affect the morphological maturation of cortical neurons in organotypic slice cultures of rat visual cortex. Expression of GCaMP3 in both time windows, and of GCaMP5G and TN-XXL in the later time window impaired apical and /or basal dendrite growth of pyramidal neurons. With time, the proportion of GECI transfectants with nuclear filling increased, but an only prolonged expression of TN-XXL caused higher levels of neurodegeneration. In multipolar interneurons, only GCaMP3 evoked a transient growth delay during the early time window. GCaMP6m and GCaMP6m-XC were quite “neuron-friendly.” Since growth-impaired neurons might not have the physiological responses typical of age-matched wildtype neurons the results obtained after prolonged developmental expression of certain GECIs might need to be interpreted with caution.